Advice for my chief resident. (4th March 2018) - Panush, Richard S.
Abstract: I have been privileged to have served as a division of rheumatology chief and/or program director for 18 years and as a department of medicine chair and medicine residency program director for another 22 years. During the latter, I collected and codified advice for my chief residents. Selected highlights are presented as follows.